2022
DOI: 10.3390/foods11081140
|View full text |Cite
|
Sign up to set email alerts
|

Caloric and Lipid Profiles in the Spanish Population of North Africa

Abstract: This study introduces an analysis for determining factors of diet quality among the Spanish adult population in North Africa with the aim of promoting healthier eating habits to prevent the development of diabetes mellitus. It is a diagnostic, non-experimental, cross-sectional and observational study, with a descriptive correlational methodology, with 201 participants from Ceuta and Melilla. The information collection has been carried out through the 24 h diet recall. Various sociodemographic factors influenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…Likewise, Izquierdo-Guerrero [41] did not find significant associations with income and CH consumption, unlike our study, which found that women with the lowest income consumed greater CH. On the other hand, according to Mohatar-Barba [71], Muslims usually eat less protein, which is similar to our results. The scarcity of studies that link sociocultural factors and diet quality in pregnant women is noteworthy.…”
Section: Discussionsupporting
confidence: 91%
“…Likewise, Izquierdo-Guerrero [41] did not find significant associations with income and CH consumption, unlike our study, which found that women with the lowest income consumed greater CH. On the other hand, according to Mohatar-Barba [71], Muslims usually eat less protein, which is similar to our results. The scarcity of studies that link sociocultural factors and diet quality in pregnant women is noteworthy.…”
Section: Discussionsupporting
confidence: 91%